Myasthenia Gravis With Thymoma, Manifesting as AChR-Ab-Positive, Distinct Bulbar Palsy Accompanied by Dysgeusia: A Case Series and Review of Literature - Zhu, Kai; Chen, Jiaxin; Li, Jingjing; Wang, Haiyan; Huang, Xin; Li, Yan; Feng, Huiyu (Frontiers in Neurology, 2018)
In this review, we summarized three cases of myasthenia gravis (MG) with taste disorder and describe their clinical features in detail. Three MG patients presented with significant bulbar palsy symptoms, high AChR-Ab titers, and negative MuSK-Ab, were diagnosed with thymoma. Furthermore, we observed that dysgeusia could manifest earlier than the occurrence of typical MG symptoms, even predict a MG relapse or a myasthenic crisis in the course of MG. We believe that dysgeusia is a non-motor symptom of MG, which especially exists in MG patients with thymoma and serious bulbar palsy. Therefore, being alert to this symptom may facilitate the early diagnosis of MG and judge the progress of the disease.